Fetal weight nomogram for Nepalese population - Joshi, Birendra Raj (Nepalese Journal of Radiology, 2018)
Introduction: Determination of fetal weight is important in all pregnancies. Accurate antenatal assessment of the fetal weight is essential for deciding the plan of management that will minimize the perinatal morbidity and mortality rate. Methods: This prospective longitudinal study was based on 221 low-risk pregnancies. Gestational age was computed from last menstrual period (LMP). Biparietal diameter (BPD), head circumference (HC), abdominal circumference (AC) and femoral length (FL) were measured using ultrasound and Estimated fetal weight (EFW) was calculated. Results: Intrauterine growth expressed by EFW showed a continuous pattern until term. Conclusion: The presented growth chart is recommended as robust reference ranges for assessing growth.